On the Oscillation of Even-Order Nonlinear Differential Equations with Mixed Neutral Terms - Mohammed K. A. Kaabar; Said R. Grace; Jehad Alzabut; Abdullah Özbekler; Zailan Siri (Journal of Function Spaces)
The oscillation of even-order nonlinear differential equations (NLDiffEqs) with mixed nonlinear neutral terms (MNLNTs) is investigated in this work. New oscillation criteria are obtained which improve, extend, and simplify the existing ones in other previous works. Some examples are also given to illustrate the validity and potentiality of our results.